1976
DOI: 10.1530/jrf.0.0480009
|View full text |Cite
|
Sign up to set email alerts
|

A difference in dry mass between the heads of X- and Y-bearing human spermatozoa

Abstract: Summary. An integrating microinterferometer was used to measure the dry mass of sperm heads. The dry mass was found to be proportional to DNA content, and thus provides a useful method of estimating sperm DNA content.Using this technique we have confirmed that human spermatozoa which show none and one quinacrine-fluorescent spot are X-and Y-bearing respectively. However, the measurements suggest that many of the spermatozoa with two quinacrine-fluorescent spots are not YY-bearing, as previously thought, but mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
6

Year Published

1976
1976
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 16 publications
1
23
0
6
Order By: Relevance
“…1981). The fre quency of nondisjunction derived from Y-body analysis did not agree with data from nuclear mass measurements (Sumner and Robinson, 1976) or from human sperm karyotypes (Brandriffand Gordon, 1990: Martin andRademaker. 1990).…”
Section: Abstract Fluorescence In Situ Hybridization (Fish) Withmentioning
confidence: 78%
“…1981). The fre quency of nondisjunction derived from Y-body analysis did not agree with data from nuclear mass measurements (Sumner and Robinson, 1976) or from human sperm karyotypes (Brandriffand Gordon, 1990: Martin andRademaker. 1990).…”
Section: Abstract Fluorescence In Situ Hybridization (Fish) Withmentioning
confidence: 78%
“…The MicroSort technique (Johnson et al 1993) uses high-speed flow cytometric sorting of individual spermatozoa based on the 2.8% greater total DNA content in normal human spermatozoa bearing an X compared with Y chromosome (Sumner and Robinson 1976). Spermatozoa are briefly exposed to a dilute solution of a nonintercalating fluorescent DNA dye (Hoechst 33342), which attaches to the minor groove of DNA (Latt and Stetten 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Shettles' method suggested that intercourse at time of ovulation, preceded by alkaline douche, female orgasm simultaneously or before the husband's orgasm, abstinence to the time of ovulation and various vaginal penetration techniques would increase the likelihood for a male offspring [1]. For the last 30 years, attention has been focused on using various in vivo techniques based on differential morphology [2,3], size and swimming ability of X-and Y-bearing spermatozoa [4]. Discontinuous albumin density gradients presented by Ericsson et al [5], Sephadex columns [6], discontinuous Percoll gradients [7] and swim-up procedures have all been widely used and researched.…”
Section: Introductionmentioning
confidence: 99%